1991
DOI: 10.1002/sia.740170609
|View full text |Cite
|
Sign up to set email alerts
|

Auger electron spectroscopy study of the surface segregation in silver–palladium alloys

Abstract: An AES study of the surface composition of silver-palladium alloys is described. The influence of sulphur contamination, matrix effects and attenuation coeflicients on the quantification of the first layer composition is discussed. The experimental Auger data are treated following the Pons et af. model. A weak silver segregation is observed and the results are compared with theoretical models and other experimental studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Moreover, from the O KLL peak, we could see that compared with silver concentration, concentrations of palladium and oxygen relatively increased. For the sample before thermal treatment (sample b), the Ag/Pd ratio was about 1:2.5, which agreed with the results from other researchers25–27 and was higher than the target ratio (Ag/Pd = 1:3.4), suggesting a silver enrichment at the top surface of the membrane. After thermal treatment (sample c), the Ag/Pd ratio changed from 1:2.5 to 1:3.4, indicating a diffusion of palladium toward the top surface during thermal treatment.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, from the O KLL peak, we could see that compared with silver concentration, concentrations of palladium and oxygen relatively increased. For the sample before thermal treatment (sample b), the Ag/Pd ratio was about 1:2.5, which agreed with the results from other researchers25–27 and was higher than the target ratio (Ag/Pd = 1:3.4), suggesting a silver enrichment at the top surface of the membrane. After thermal treatment (sample c), the Ag/Pd ratio changed from 1:2.5 to 1:3.4, indicating a diffusion of palladium toward the top surface during thermal treatment.…”
Section: Resultssupporting
confidence: 89%
“…Surface compositions of different alloys can be predicted by phase diagrams from different empirical models including the ideal solution, real solution, embedded atom [30], or from first principles calculations that have been done by Johansson and coworkers [10,31]. The phase diagrams of the ideal solution model and the first principle studies share similar qualitative features and reasonably predict the experimental surface segregation of AgPd alloys leading to low Pd surface concentrations [32,33].…”
Section: Voltammetry Of Agpd(111) Alloysmentioning
confidence: 92%
“…Results from AgPd alloy surface compositions experiments described in the literature vary considerably for a certain bulk composition due to the different alloy preparation [30,32,33]. Besides on the surface orientation [31,34], the equilibrium surface composition is strongly dependent on the annealing temperature [10,33].…”
Section: Voltammetry Of Agpd(111) Alloysmentioning
confidence: 97%
“…Our measurements of the H 2 –D 2 exchange kinetics across Ag x Pd 1– x composition space occurred in an H 2 -rich environment at atmospheric pressure. While surface enrichment of Ag is reported for Ag x Pd 1– x alloys under vacuum and inert atmospheres due to its lower surface free energy, , inverse surface segregation phenomena have been reported both experimentally and computationally , for Ag x Pd 1– x alloys in H 2 -rich atmospheres. In fact, we have recently shown that a Ag x Pd 1– x CSAF nearly identical to the one studied here could be activated for ethylene hydrogenation by inducing inverse surface segregation phenomena using trace amounts of a spectator species in the reaction mixture .…”
Section: Discussionmentioning
confidence: 99%